Bridging School and Career: The Impact of Work-Based Learning on Career Adaptability: Menjembatani Sekolah dan Karier: Dampak Pembelajaran Berbasis Kerja terhadap Adaptabilitas Karier - Mochamad Randy Pradika Rakasiwy (Sultan Idris Journal of Psychology and Education, 2025)
The rapid transformation of the global labor market requires vocational education graduates to possess high career adaptability. This study investigates the relationship and influence of work-based learning on the career adaptability of vocational high school students in Surabaya. Employing a quantitative correlational design, data were collected from 101 final-year students participating in structured work-based learning programs, measured using the Career Adapt-Abilities Scale (CAAS) and a work-based learning participation questionnaire. Descriptive statistics, pearson correlation, and simple linear regression were applied to test the hypotheses. Results revealed a strong positive correlation between work-based learning and career adaptability (r = 0.716, p < 0.001), with work-based learning explaining 64% of the variance in adaptability scores. Curiosity emerged as the highest dimension, while concern and confidence remained moderate. These findings align with experiential learning and career construction theories, highlighting that authentic workplace engagement supported by structured mentoring, diverse tasks, and integration with school learning enhances the psychosocial resources necessary for managing career challenges. Practically, improving work-based learning quality through greater task variety, intensive mentoring, and structured reflection can better prepare adaptive, resilient, and work-ready graduates.